COMPARISON OF MODE OF DELIVERY IN UNDIAGNOSED BREECH PRESENTATION IN LABOUR - Karim, Rukhsana; Jabeen, Sadaqat (Journal of Postgraduate Medical Institute, 2013)
Objective: To compare vaginal delivery and cesarean section in terms of neonatal morbidity and mortalityin undiagnosed breech presented in labour. Methodology: This comparative study was conducted at Department of Obstetrics and Gynaecology, LadyReading Hospital Peshawar from January to December 2011. Total of 119 undiagnosed breeches admittedin labour ward were included in the study. Apart from the demographic details neonatal outcome includingApgar score, intrapartum fetal death and neonatal intensive care unit admission were recorded on a semistructured proforma and analyzed by Chi square test using SPSS v. 17. Results: The mean age of the women delivered vaginally was 27.91+6.37 years while the mean age ofthose that underwent cesarean section was 23.88+3.32 years. The overall mean age of the sample was27.03+6.06 years. The mean gestational age of the fetuses in both the groups was between 37-40 weeks.Out of 93 breeches which were delivered vaginally, 12(12.9%) neonates were having Apgar score <7.Whilethose delivered by cesarean section only 2(2.1%) neonates were having low Apgar score (p-value=0.511).Two(2.1%) neonates were admitted in neonatal intensive care unit in the vaginally delivered group, whileamong in the cesarean section group there was no neonatal intensive care unit admission(pvalue=0.462).There was no intrapartum death in both the groups. Conclusion: Undiagnosed, uncomplicated breeches presenting in labour can be safely delivered vaginally,but large randomized study is needed to decide about the best mode of delivery.